The INFLUENCE OF JOB INSECURITY , WORK MOTIVATION, ORGANIZATIONAL COMMITMENTS AND WORK SATISFACTION AS INTERVENING VARIABLES TO EMPLOYEE PERFORMANCE : Case Study of PT Semar Beton Perkasa, Tuban Regency - Drs. H. Dasuki. M.Pd, Novi Lailatun Nikmah (Archives of Business Research, 2019)
ABSTRACT The purpose of this study is to analyze and interpret the effect of job insecurity , work motivation, organizational commitment and job satisfaction on employee performance. The population in this study were employees of PT Semar Beton Perkasa in Tuban Regency totaling 7 people . In this study the sampling used a saturated sampling technique . A number of samples equals the total population, which is 7 0 people . For this study data analysis used the Partial Least Square (PLS) approach . The results of the study show that job insecurity , work motivation, organizational commitment and job satisfaction have a significant effect on employee performance